Processing Stabilization of Polyethylene with Grape Peel Extract: Effect of Extraction Technology and Composition - Kata Takács; Emese Pregi; Erika Vági; Tibor Renkecz; Dóra Tátraaljai; Béla Pukánszky (Molecules, 2023)
Dry grape peel powder was extracted by three different techniques, stirred tank reactor, Soxhlet and ultrasound extraction. The composition, physical and chemical structure and inherent stability of the extracts were characterized by various methods. The extracts and reference compounds were added to polyethylene and their stabilization efficiency was determined in multiple extrusion experiments. The composition of the extracts was quite similar. Ten main compounds were identified in the extracts, which contained a considerable number of polyphenols, but only small amounts of quercetin and trans-resveratrol. The extracts proved to be more efficient processing stabilizers than trans-resveratrol and the commercial stabilizer, Irganox 1010, irrespective of the extraction technology used. In spite of their good processing stabilization effect, polymers containing the extracts had poor residual stability. The differences in processing and long-term stabilization must be related to the different structures of the polyphenols contained by the extracts and the reference compounds. The results clearly prove that the IC50 value determined by the DPPH assay is not suitable for the estimation of the efficiency of a compound as a stabilizer for polymers.